Avaliação da biodegradabilidade de efluentes têxteis do beneficiamento secundário de malhas de poliéster tratados com Reagente de Fenton Biodegradability evaluation of textile effluents from the secundary process of polyester fibers treated with Fenton's Reagent - Dângelle M. Oliveira; Mônica M. D. Leão (Química Nova, 2009)
From the environmental point of view, the textile sector is outstanding for the generation of large amounts of biorecalcitrant effluents. In this paper the textile effluent biodegradability, both before and after its treatment with Fenton's Reagent, were compared by means of biologic tests. These tests showed that the Fenton treatment lowered the biodegradabilty of practically all tested effluents, except one specific effluent from a scouring bath of polyester fibers, which achieved a 93% COD removal. This removal was due to a significant phase separation (oil/water).